Infrared spectroscopy of volcanoes: from laboratory to orbital scale - Williams, Daniel B.; Ramsey, Michael S. (Frontiers in Earth Science, 2024)
Understanding the composition, texture, and morphology of volcanic rocks erupted at the surface better constrains the eruption style, as well as being a vital resource to infer subsurface processes, the development of a magma upon ascent, and the potential for future eruptions. Reflectance and emission spectroscopy of these rocks collected from the near infrared (NIR) through the thermal infrared (TIR) portion of the electromagnetic (EM) spectrum provides the data necessary to retrieve composition, micron-scale surface roughness, and particle size. Remote imaging systems enable the ability to analyze active volcanoes in remote regions, where sample collection for laboratory analysis poses a significant challenge. Laboratory hyperspectral data of samples acquired at volcanic deposits are easily resampled to the spectral resolution of any infrared sensor, and provide a means of estimating the composition of volcanoes and their products worldwide, as well as those on other planetary bodies such as the Moon and Mars. In this review paper, we provide an overview of the current use of infrared reflectance and emission spectroscopy as an analysis tool in volcanology, including ground-based imaging systems that acquire unprecedented detail and serve as testbeds for new orbital concepts. We also discuss the potential impact that future satellite missions will have on volcano science as the spectral, spatial, and temporal resolutions improve.